Implementasi Manajemen Strategis dalam Pengembangan Sekolah Dasar: Studi Kasus di SDN 006 Buahbatu Bandung - Marisan, Susan; Iriantara, Yosal (Jayapangus Press, 2025)
This study investigates the implementation of strategic management in the development of SDN 006 Buahbatu, an elementary school in Bandung City, West Java, responding to institutional challenges in school planning and performance improvement. Using a qualitative case study method, the research adopts the strategic management framework by Wheelen and Hunger, comprising environmental scanning, strategy formulation, implementation, and evaluation. Data were collected through interviews, document analysis, and school performance reports. The findings show that contextual adaptation of strategic management—beginning with internal analysis of teacher capacity and external scanning of community characteristics—strengthens institutional planning, enhances instructional quality, and improves student outcomes. Notably, students' final exam scores increased by 20%, while student motivation and engagement rose by 75%. These results highlight the academic significance of integrating strategic management processes in primary education, particularly when inclusive planning and collaborative leadership are prioritised. The study contributes to the limited empirical literature on strategy application in primary schools by demonstrating a practical model for stakeholder-based institutional development. It offers both theoretical insight into context-responsive management practices and practical guidance for school leaders seeking sustainable improvement. Further research is recommended to examine comparative models across multiple institutions and to employ mixed methods for broader generalisation.